LeRoy's The Americans in the Philippines and the history of Spanish rule in the Philippines - Cano, Glòria (2013)
James A. LeRoy emerged in 1905 as an authority on Philippine history. In The Americans in the Philippines, LeRoy’s chapter on the Spanish regime showed his unmatched acquaintance with Spanish and English sources. But his knowledge of Spanish historiography enabled him to suppress important works on the last thirty years of Spanish rule, particularly those dealing with reforms, thereby shaping the image of a “dark age” of medievalism dominated by religious orders. This article explores the significance of LeRoy’s book in shaping American colonial discourse and criticizes LeRoy’s idea of a “dark age” by introducing part of the bibliography he omitted.
Keywords: Philippines -- History -- Revolution, 1899-1901; LeRoy, James A., 1875-1909